Efeitos redox ativos do carvacrol em modelos experimentais in vitro - Chenet, Aline Lukasievicz (2018)
The mitochondria are organelles presenting double-membrane and are the main sites of adenosine triphosphate (ATP) production. The electron transfer chain generates an electrochemical gradient in the intermembrane space, which is utilized by the complex V (ATP syntase/ATPase) to produce ATP from adenosine diphosphate and inorganic phosphate. Mitochondrial dysfunction plays a central role in redox impairment and inflammation. Disruption in the respiratory chain activity leads to increased rates of reactive oxygen species consequently enhancing the levels of markers of oxidative stress. Moreover, there are evidences that mitochondria produce reactive nitrogen species during both acute and chronic phases of stress. Indeed, the mitochondria are the major site of production of reactive species in human cells. The utilization of natural or synthetic molecules to prevent or to treat mitochondrial dysfunction has been viewed as an interesting pharmacological strategy in the case of neurodegenerative diseases. The high rates of neuronal loss lead to cognitive impairment and decrease the life quality of the patients suffering from those diseases. In this context, carvacrol has been demonstrated to induce antioxidant and anti-inflammatory effects in several experimental models. However, it was not previously demonstrated whether and how carvacrol would promote mitochondrial protection in human cells. Therefore, we investigated here whether a pretreatment (for 4 h) with carvacrol at 10 - 1000 µM would be able to prevent mitochondrial dysfunction in the human neuroblastoma cells SH-SY5Y in an experimental model of redox impairment induced by hydrogen peroxide. We found that the pretreatment with carvacrol at 100 µM decreased the levels of redox stress markers in the membranes of mitochondria obtained from the hydrogen peroxide-treated cells. The carvacrol was also efficient in reducing the impact of hydrogen peroxide in the mitochondrial function, since this natural compound prevented the decrease in the activity of the complexes I and V, as well as of the enzymes aconitase, -ketoglutarate dehydrogenase, and succinate dehydrogenase. Carvacrol also attenuated the mitochondrial production of the radical anion superoxide and the total production of nitric oxide in this work. Carvacrol also prevented the pro-inflammatory state induced by hydrogen peroxide by reducing the levels of the cytokines interleukin1 and tumor necrosis factor-. The carvacrol inhibited the nuclear factor-B, which XII is the master regulator of the immune response in human cells. The abovementioned effects elicited by carvacrol were suppressed by the inhibition of the cytoprotective enzyme heme oxygenase-1. Therefore, we suggest that heme oxygenase-1 is involved in the modulation of the carvacrol-induced mitochondrial protection seen in this experimental model.